What you see is what you remember? Depictions of historical figures influence memory for historical facts. (December 2017) - Merkt, Martin; Schwan, Stephan
Abstract: We investigated whether the characteristics of pictures affect memory for verbal learning materials. In the learning phase, participants watched a slideshow about historical figures that were depicted as more or as less powerful. The slideshow included spoken information that was more prototypical for either powerful or powerless people and thus semantically congruent (e.g., depiction and verbal information rated as powerful) or incongruent with the pictures. Congruency resulted in more errors when participants had to reject incorrect items in a memory test. There was no effect of congruency on verifying correct items. This pattern was observed for a slideshow that included one picture for each historical figure (Experiment 1) and for a slideshow including additional pictures (Experiment 2). Hence, both experiments provide corroborating evidence that pictures affect learners' memory for verbal learning materials. These findings are relevant for instructional practice with regard to the design of learning materials and test items. Highlights: Implicit meanings in pictures affect memory for verbal statements. Congruency of text and picture resulted in fewer rejections of incorrect items. No effect of congruency was observed for correct items. The central findings were replicated across two experiments.